Impact of Dividend Policy on Stock Price Movements of State-Owned Banks: The Case of BBRI in FY2024 - Maykada Harjono; Nugraha; Moh. Wildan; Hendi Herdiyana (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This research examines how dividend policy influences stock price movements of PT Bank Rakyat Indonesia (BBRI) during the 2024 fiscal year. The study applies a quantitative method using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze trading behavior and market sentiment around the ex-dividend period. The findings show that dividend policy has a positive and significant relationship with stock prices, mainly driven by trading activity rather than market sentiment. The model demonstrates strong explanatory power in describing stock performance during the observation period. These results support the Signaling Theory and Bird in Hand Theory, suggesting that a stable and transparent dividend policy reflects corporate strength and credibility. Consequently, dividends serve as an important communication tool that enhances investor confidence and maintains positive market perceptions toward state-owned banks such as BBRI. Keywords: Dividend Policy; IDX Stocks; Market Sentiment; BBRI; PLS-SEM